2017
DOI: 10.22317/jcms.09201705
|View full text |Cite
|
Sign up to set email alerts
|

Stature estimation from forearm length: an anthropological study in Iranian medical students

Abstract: Objective Stature estimation is an important biological factor for forensic medicine to identify an individual. Forearm length can be used for the prediction of the stature in different populations. In the present study, the relation between forearm length and height was evaluated. Methods In a cross sectional study, a sample of 100 males and 100 females (aged 18 to 25 years) medical students from Iranian population was randomly entered into the study. Left forearm was measured by measuring tape. Stature was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Several studies have reported the population differences in anthropometric measurements [18,19]. Besides, our previous studies have confirmed the population differences in Iran [17,20,21].…”
Section: Introductionsupporting
confidence: 69%
“…Several studies have reported the population differences in anthropometric measurements [18,19]. Besides, our previous studies have confirmed the population differences in Iran [17,20,21].…”
Section: Introductionsupporting
confidence: 69%
“…Several studies have been performed on some bones for stature and sex estimation in the Iranian population. Poorhassan et al, in a cross-sectional study of Iranian medical students aged 18 -25 years, reported that forearm length is a moderate predictor of stature (15). In another study of 19-21-year-old Iranian medical students, Navid et al stated that arm length is reliable for stature prediction (13).…”
Section: Introductionmentioning
confidence: 99%